2015
DOI: 10.1002/2015jc011264
|View full text |Cite
|
Sign up to set email alerts
|

Using Lagrangian‐based process studies to test satellite algorithms of vertical carbon flux in the eastern North Pacific Ocean

Abstract: The biological carbon pump is responsible for the transport of ∼5–20 Pg C yr−1 from the surface into the deep ocean but its variability is poorly understood due to an incomplete mechanistic understanding of the complex underlying planktonic processes. In fact, algorithms designed to estimate carbon export from satellite products incorporate fundamentally different assumptions about the relationships between plankton biomass, productivity, and export efficiency. To test the alternate formulations of export effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 62 publications
4
66
0
Order By: Relevance
“…Maiti et al (2013) conducted a similar comparison between 234 Th-and satellite-derived C export in the Southern Ocean and observed a 2 to 4-fold overestimation of C export using the L11 and D05 models, with NPP obtained from the VGPM and the CbPM models. Stukel et al (2015) found similar results in the eastern North Pacific Ocean. In the North Western Atlantic Ocean, we observe that D05 tends to significantly overestimate C export relative to in situ estimates in the equatorial domain, whereas L11 appears to underestimate C export, mainly in the northern half of the oligotrophic domain and at several riverine stations.…”
Section: Comparison With Satellite-based Export Modelssupporting
confidence: 75%
“…Maiti et al (2013) conducted a similar comparison between 234 Th-and satellite-derived C export in the Southern Ocean and observed a 2 to 4-fold overestimation of C export using the L11 and D05 models, with NPP obtained from the VGPM and the CbPM models. Stukel et al (2015) found similar results in the eastern North Pacific Ocean. In the North Western Atlantic Ocean, we observe that D05 tends to significantly overestimate C export relative to in situ estimates in the equatorial domain, whereas L11 appears to underestimate C export, mainly in the northern half of the oligotrophic domain and at several riverine stations.…”
Section: Comparison With Satellite-based Export Modelssupporting
confidence: 75%
“…Both models and in situ data suggest that this production−export imbalance results, in part, from lateral transport of particles produced in the coastal area to the offshore region where net export is expected (20)(21)(22)(23). However, the expected high export ratio in offshore waters of the CCE is not supported by existing in situ measurements (19,24).…”
mentioning
confidence: 92%
“…Knowing phytoplankton size distribution and functional type together are first steps toward characterizing pelagic food webs (e.g., Michaels and Silver, 1988). It has been shown recently that the performance of the Siegel et al (2014) export flux model improves substantially if the parameters are regionally tuned supporting the importance of food web structure (Stukel et al, 2015). Further, recent field data summaries show strong relationships between the vertical scales of sinking flux attenuation in the TZ and both phytoplankton community structure in the EZ (Guidi et al, 2015;Puigcorbé et al, 2015) and environmental conditions in the TZ (Marsay et al, 2015).…”
Section: Carbon Export From the Euphotic Zone And Its Fate Within Thementioning
confidence: 99%